DOWNWARD SOCIAL MOBILITY IN THE USSR: THE CASE OF DISSIDENTS (Південний архів (історичні науки), 2024)
Purpose. The purpose of the study is to analyze the causes and consequences of downward social mobility in the Ukrainian SSR based on the memoirs of dissidents. Methods. The work uses general scientific methods of analysis and comparison, which allowed to identify the channels of social mobility in different social strata of Soviet society; the systematic method was used to identify the factors of social mobility in the Ukrainian SSR. The historical method made it possible to consider the problem of social elevators and the directions of their movement in specific historical conditions. Since the main source of the study was the memoirs of Ukrainian dissidents, the hermeneutic method was used. At the same time, the biographical method, through the disclosure of certain aspects of a person's life, allowed for a generalized analysis of the problem of downward social mobility and empirical support for the theoretical positions put forward in the article. Results. The study found that horizontal (spatial) social mobility in the USSR was complicated by restrictions imposed by the state (passport, residence permit). The most effective social elevators in the USSR were education and the army. The relationship between class origin and social mobility is established. It is shown that a change in the social status of a person was not always a condition for changing his or her financial situation. The study of the memoirs of Ukrainian dissidents revealed that most of them came from peasant or working-class families. Their channel of social upward mobility was education. However, a prerequisite was participation in the Komsomol, and later membership in the CPSU. Conclusions. Both upward and downward social mobility was controlled by the state. The social descent was forced and was accompanied by the loss of work and housing, as well as the opportunity to engage in professional activities. In the case of dissidents, family and marriage, in the conditions of loss of social status, led to the social degradation of one or all family members.
Keywords: social ladder, social channels, dissidents, Ukrainian SSR, financial situation, social status